2020
DOI: 10.1109/access.2020.3008429
|View full text |Cite
|
Sign up to set email alerts
|

A Wide Incident Angle, Ultrathin, Polarization-Insensitive Metamaterial Absorber for Optical Wavelength Applications

Abstract: Polarization-insensitive metamaterial absorbers (MMAs) are currently attracting a great deal of interest throughout the optical region. These kinds of MMAs can be used as energy harvesting, thermal imaging, plasmonic sensor, magnetic imaging, light trapping, optical modulator, and can help to decipher an inherence for the field. Here, a polarization-insensitive ultrathin MMA has been proposed with an extensive incident angular stability for the optical region with a sandwiched three-layer structure. Tungsten (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 120 publications
(110 reference statements)
0
18
0
Order By: Relevance
“…The insensitivity of absorption characteristics facing various incident waves is an important parameter due to different polarization and incident angles. Some reported designs show a perfect insensitivity facing different polarization and incident angles for a broad spectrum 49 , 50 . However, having a high Q-factor followed by sharp resonance is crucial for sensing applications.…”
Section: Mpa Simulation Resultsmentioning
confidence: 99%
“…The insensitivity of absorption characteristics facing various incident waves is an important parameter due to different polarization and incident angles. Some reported designs show a perfect insensitivity facing different polarization and incident angles for a broad spectrum 49 , 50 . However, having a high Q-factor followed by sharp resonance is crucial for sensing applications.…”
Section: Mpa Simulation Resultsmentioning
confidence: 99%
“…The reason for this kind of variation is the different refractive indices of those materials. As we know, for visible to nearinfrared metamaterial absorbers, the lower the refractive index, the higher the absorption and the more extensive the bandwidth [7]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Perfect absorbers (PA) based on metamaterials have been the subject of intensive research in recent years owing to their various potential applications in infrared stealth, daytime radiative cooling, solar energy, and thermal imaging, among others [1][2][3][4][5][6][7][8][9]. In 2008, Landy et al reported the first metamaterial PA functioning in the gigahertz (GHz) range [10].…”
Section: Introductionmentioning
confidence: 99%
“…These plasmons on the surface provided the ideal dipole for the magnification of the located E-field. The interfaces between aluminum and GaAs increase the surface plasmon in the MA which led it to high absorption in some particular points [17], [67]. The electrical dipolar resonance moment is stimulated by the e-field which is strongly confined in the dielectric substance GaAs layer evident in Fig.…”
Section: G Electric Fields Magnetic Fields and Surface Current Densitymentioning
confidence: 98%
“…Generally, a three-layered metal-dielectric-metal structure is supposed to be near PMA in solar wavelength. Metal layers prevent the propagation of the EM waves, and a coupling capacitance is constructed between the backlayer and the resonator in an MA with the help of a dielectric substance [17], [18]. Plasmonic resonance characteristics of a dielectric substrate [19], [20], perfect impedance match [21], [22], symmetric structure of the resonator [23], [24], and a good E-field, H-field and surface charge distribution [25], [26] causes high absorption of an PMA.…”
Section: Introductionmentioning
confidence: 99%